2010
DOI: 10.3171/2009.6.jns09716
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions of awake and outpatient craniotomy for brain tumor: a qualitative study

Abstract: The results reflected positively on the patients' awake and outpatient surgery experience, but there were some areas that require improvement, specifically perioperative pain control and postoperative care. These insights on patients' perspectives can lead to better delivery of care, and ultimately, improved health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
109
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(130 citation statements)
references
References 6 publications
9
109
0
9
Order By: Relevance
“…18 However a previous study by our group demonstrated low degrees of anxiety and high levels of satisfaction. 22 Our present study aims to acquire a better understanding regarding music and its role in helping to ameliorate surgically related stress and optimize overall hospital experience for patients undergoing awake craniotomy.…”
mentioning
confidence: 99%
“…18 However a previous study by our group demonstrated low degrees of anxiety and high levels of satisfaction. 22 Our present study aims to acquire a better understanding regarding music and its role in helping to ameliorate surgically related stress and optimize overall hospital experience for patients undergoing awake craniotomy.…”
mentioning
confidence: 99%
“…In contrast to the previous research described, two recent studies, conducted in Canada (Khu et al 2009) …”
Section: Qualitative Studiesmentioning
confidence: 56%
“…33,34 Patients who undergo awake surgery would presumably like to do so because they believe it will improve outcomes and minimize complications. 15 Undoubtedly, they would be surprised and dismayed to learn that factors never disclosed to them influenced their surgeon to recommend the procedure. Most patients trust their surgeon and follow the recommended course of action so the responsibility is the surgeon's to be open and fair with his/her recommendation.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 Patients have reported that having brain surgery done as outpatients made their disease seem less serious, which contributed to emotional well-being and aided in the recovery process. 15 Although a strong argument can be made for performing awake craniotomy on tumors regardless of the proximity to eloquent cortex, as well as on an outpatient basis, to do so means some patients will form a part of the neurosurgeon's learning curve. In other words, they will be used as practice for the benefit of others.…”
Section: Surgical Innovationmentioning
confidence: 99%
See 1 more Smart Citation